2018
DOI: 10.1002/wnan.1509
|View full text |Cite
|
Sign up to set email alerts
|

Silk nanofibril self‐assembly versus electrospinning

Abstract: Natural silk fibers represent one of the most advanced blueprints for (bio)polymer scientists, displaying highly optimized mechanical properties due to their hierarchical structures. Biotechnological production of silk proteins and implementation of advanced processing methods enabled harnessing the potential of these biopolymer not just based on the mechanical properties. In addition to fibers, diverse morphologies can be produced, such as nonwoven meshes, films, hydrogels, foams, capsules and particles. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 259 publications
(423 reference statements)
0
25
0
Order By: Relevance
“…For clinical use, removal of sericin from silk by degumming is essential because sericin has traditionally been linked to the inflammatory response reported for virgin silk [ 20 , 21 ]. SFNFs have often been prepared based on the electrospinning of silk fibroin solutions obtained by dissolution through the decomposition of the β-sheet structure of silk fibroin that contributes to the mechanical robustness of native silk fibers [ [22] , [23] , [24] ]. However, obtaining SFNFs by mechanical disintegration of degummed silk fibers is simpler and less energy- and time-consuming than preparation of SFNFs by electrospinning [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For clinical use, removal of sericin from silk by degumming is essential because sericin has traditionally been linked to the inflammatory response reported for virgin silk [ 20 , 21 ]. SFNFs have often been prepared based on the electrospinning of silk fibroin solutions obtained by dissolution through the decomposition of the β-sheet structure of silk fibroin that contributes to the mechanical robustness of native silk fibers [ [22] , [23] , [24] ]. However, obtaining SFNFs by mechanical disintegration of degummed silk fibers is simpler and less energy- and time-consuming than preparation of SFNFs by electrospinning [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of silk-like domains confers the engineered SELR with the ability to self-assemble into fibrillary structures via H-bonded nanocrystalline β-sheet structures (Sun and Marelli, 2020). As such, fibrillary morphogenesis, which is not a prevailing feature of the ELRs (Misbah et al, 2015) but has been successfully imitated by the use of electrospinning techniques (Humenik et al, 2018), can be genetically encoded into the SELR constructs, thus conferring the inherent ability to form fibers comprising bundles of fibrils (Tarakanova and Buehler, 2012). In addition, molecular modeling has demonstrated that the thermoresponsive behavior of the elastin-like sequences is preserved in the SELR and favors the silk β-sheet assembly process (Tarakanova et al, 2017).…”
Section: Silk-elastin-like Recombinamers (Selrs) and Silk-tropoelastin Biomaterialsmentioning
confidence: 99%
“…Apart from the assemblies discussed above, many natural fibrous proteins with remarkable chemical, optical, mechan-ical, electrical and electromagnetic properties have been studied. Elastins, [98][99][100] collagens, [101][102][103] (Figure 7A, B) silks, [49,[104][105][106] keratins, [107][108][109] resilins, [110] and amyloid peptides and proteins [111][112][113][114] (Figure 7C) are the most common structural proteins having a set of convenient properties considered for protein-based bionanomaterial synthesis not only at 1D, but also in highly ordered scales. [16,[115][116][117] These families of proteins are characterized by long-range ordered molecular secondary structures (e. g., β-pleated sheets, coiled coils, or triple helices) that arise from the highly repetitive primary amino acid sequences within the proteins.…”
Section: D-materials: Protein Strings Rings and Fibrilsmentioning
confidence: 99%
“…Apart from the assemblies discussed above, many natural fibrous proteins with remarkable chemical, optical, mechanical, electrical and electromagnetic properties have been studied. Elastins, [98–100] collagens, [101–103] (Figure 7A, B) silks, [49,104–106] keratins, [107–109] resilins, [110] and amyloid peptides and proteins [111–114] (Figure 7C) are the most common structural proteins having a set of convenient properties considered for protein‐based bionanomaterial synthesis not only at 1D, but also in highly ordered scales [16,115–117] …”
Section: Self‐assembled Protein Materialsmentioning
confidence: 99%